A correlative evaluation of morphology and rheology of Aspergillus terreus during lovastatin fermentation - Gupta K.; Mishra P.K.; Srivastava P. (My University, 2025)
Lovastatin, a secondary metabolite, was produced by fermentation process using Aspergillus terreus in an internal loop airlift reactor. It is a highly aerobic fermentation process. Biomass concentration and cell morphology were evaluated and observed to contribute significantly to the high viscosity and pseudoplastic non-Newtonian behavior of the broth. Typical morphological changes over 10 days in the fermentation broth were studied. The viscosity increased from the start of the fermentation with an increasing cell mass content, reached to a maximum of 60 N/m2·s at 160 h and then declined after the branching of the hyphae with the formation of arthrospores. Rheological parameters like consistency index and fluidity index were evaluated. The consistency index was observed to increase from 9.8 to 66.85 N/m2, while fluidity index decreased from 0.69 to 0.48 s-1 during 10 days of lovastatin production. A correlation between growth and consistency index of the broth has been evaluated. © KSBB.